Transcriptome analyses of Atlantic salmon muscle genes induced by a DNA vaccine against salmonid alphavirus, the causative agent of salmon pancreas disease (PD) - Sobhkhez, Mehrdad; Krasnov, Aleksei; Robertsen, Børre (PLOS ONE, 2018)
The following article, Sobhkhez, M., Krasnov, A. & Robertsen, B. (2018). Transcriptome analyses of Atlantic salmon muscle genes induced by a DNA vaccine against salmonid alphavirus, the causative agent of salmon pancreas disease (PD). PLoS ONE , 13:e0204924(10). https://doi.org/10.1371/journal.pone.0204924, can be accessed at https://doi.org/10.1371/journal.pone.0204924 . Salmonid alphavirus (SAV) is the causative agent of pancreas disease (PD) in farmed Atlantic salmon. A previous study showed that vaccination of pre-smolt salmon with a plasmid encoding the structural polypeptide of SAV gave protection against infection and development of PD accompanied by production of antibodies against the virus. In the present work we analyzed transcript responses in the muscle to vaccination with this plasmid (here named pSAV). The purpose was to shed light on how pSAV might initiate adaptive immune responses in the fish. The work was based on microarray and reverse transcription quantitative PCR analyses of muscle at the injection site 7 days after vaccination. The results showed that pSAV and pcDNA3.3 had similar abilities to up-regulate type I IFN stimulated genes. In contrast, pSAV caused higher up-regulation of IFNγ and several IFNγ inducible genes. Compared to pcDNA3.3, pSAV also gave larger increase in transcripts of marker genes for B-cells, T-cells and antigen presenting cells (APCs), which suggest attraction and role of these cells in the adaptive immune responses elicited by pSAV. Moreover, pSAV caused a stronger up-regulation of the chemokine CXCL10 and the proinflammatory cytokines IL-1ß and TNFα, which may explain attraction of lymphocytes and APCs. The present work shows that the expression profile of genes resulting from vaccination with pSAV is different from the expression profiles obtained previously by vaccination of salmonids with DNA vaccines against infectious salmon anemia virus and infectious hematopoietic necrosis virus.